IMPLEMENTASI ALGORITMA FP-GROWTH UNTUK PENENTUAN REKOMENDASI PRODUK UMKM BERDASARKAN FREKUENSI PEMBELIAN - Rd.M.Dimas Burhanudin Akbar; Pritasari Palupiningsih; Budi Prayitno (Jurnal Teknoinfo, 2023)
The rapid growth of the MSMEs business is caused by the development of digital technology that makes it easy to open a business. Business competition is a challenge for MSMEs, to be able to survive in business competition, it is necessary to make the right business decisions in order to maximize the business potential of MSME. One way that MSMEs can do in order to maximize business potential is by providing the right product recommendations to consumers. The right product is obtained by analyzing consumer purchasing patterns. This research uses the association rule technique and the FP-Growth algorithm to get the right rule as a product recommendation for MSME. The analysis uses transaction data on MSME from January 1, 2021 to April 30, 2021, obtained 1483 transactions with 3 trials at a minimum support of 1%, 2%, and 3% and a minimum confidence of 30%. To determine the correlation found in the rules formed, a lift ratio was used. In the first experiment, 13 rules were found that had a lift ratio value > 1 of the 24 rules formed. The rule that has the highest lift ratio value is if you buy Strawberry Tea, you buy Kopi Susu Pagi, and Mineral Water of 6.9. In the second experiment, there were 3 rules that had a lift ratio value > 1 of the 6 rules formed, the rule that had the highest lift ratio value, namely, if you buy strawberry tea, you buy mineral water of 3.69. In the third experiment, there was no rule that had a lift ratio value > 1. The established rules could be the basis for MSME in providing the right product recommendations to consumers.